Peak Velocity as an Alternative Method for Training Prescription in Mice - Picoli, Caroline de Carvalho; Romero, Paulo Vitor da Silva; Gilio, Gustavo R.; Guariglia, Débora A.; Tófolo, Laize P.; de Moraes, Solange M. F.; Machado, Fabiana A.; Peres, Sidney B. (Frontiers in Physiology, 2018)
Purpose: To compare the efficiency of an aerobic physical training program prescribed according to either velocity associated with maximum oxygen uptake (vVO2max) or peak running speed obtained during an incremental treadmill test (Vpeak_K) in mice. Methods: Twenty male Swiss mice, 60 days old, were randomly divided into two groups with 10 animals each: a group trained by vVO2max (GVO2) and other group trained by Vpeak_K (GVP). After the adaptation training period, an incremental test was performed at the beginning of each week to adjust training load and to determine the amount of VO2 and VCO2 fluxes consumed, energy expenditure (EE) and run distance during the incremental test. Mice were submitted to 4 weeks of aerobic exercise training of moderate intensity (velocity referring to 70% of vVO2max and Vpeak_K) in a programmable treadmill. The sessions lasted from 30 to 40 minutes in the first week, to reach 60 minutes in the fourth week, in order to provide the mice with a moderate intensity exercise, totaling 20 training sessions. Results: Mice demonstrated increases in VO2max (ml•kg˗0,75•min˗1) (GVO2 = 49.1% and GVP = 56.2%), Vpeak_K (cm•s-1) (GVO2 = 50.9% and GVP = 22.3%), EE (ml•kg˗0,75•min˗1) (GVO2 = 39.9% and GVP = 51.5%), and run distance (cm) (GVO2 = 43.5% and GVP = 33.4%), after 4 weeks of aerobic training (time effect, P > 0.05); there were no differences between the groups. Conclusions: Vpeak_K has practical implications for researchers aiming to collect data concerning the effects of training due to its low cost, which is made possible by the fact that it does not require expensive equipment (i.e., gas analyzer).